Information design challenges for digital inclusion of older adults from the perspective of health literacy: a scoping review - Fragelli, Thaís Branquinho Oliveira; Oliveira, Junior Arthur Campêlo de; Machado , Vitor Pedra; Garcia , Kerolyn Ramos; Pereira , Leonardo Costa; Karnikowski , Margô Gomes de Oliveira; Areda , Camila Alves (InfoDesign, 2024)
With the increasing access to digital resources, the use of these for monitoring and self-managing health conditions can be promising. However, for the effective integration of these technologies into health routines, it is crucial to identify user skills and resources, as well as to develop strategies that meet user needs. The aim of this study was to identify the kinds of literacy needed for elderly people to use healthcare applications. A scoping review was conducted, guided by the JBI Evidence Synthesis methodology, and the PRISMA-ScR was used. Nineteen studies were selected, ranging from 2014 to 2024, divided into the categories of computer literacy, information literacy, media literacy, and health literacy. The studies found indicate the need for future research to enhance methods for evaluating, improving usability, and promoting accessibility of health applications for elderly people.